Parabola-Like Gold Nanobowtie on Sapphire Substrate as Nano-Cavity - Wenbing Li; Zhuo Yang; Jiali Zhang; Xin Tong; Yuheng Zhang; Bo Liu; Chao Ping Chen (Photonics, 2022)
Plasmonic metallic nanostructures have attracted much interest for their ability to manipulate light on a subwavelength scale and for their related applications in various fields. In this work, a parabola-like gold nanobowtie (PGNB) on a sapphire substrate was designed as a nano-cavity for confining light waves in a nanoscale gap region. The near-field optical properties of the innovative PGNB structure were studied comprehensively, taking advantage of the time-resolved field calculation based on a finite-difference time-domain algorithm (FDTD). The calculation result showed that the resonance wavelength of the nano-cavity was quite sensitive to the geometry of the PGNB. The values that related to the scattering and absorption properties of the PGNB, such as the scattering cross section, absorption cross section, extinction cross section, scattering ratio, and also the absorption ratio, were strongly dependent on the geometrical parameters which affected the surface area of the nanobowtie. Increased sharpness of the gold tips on the parabola-like nano-wings benefited the concentration of high-density charges with opposite electric properties in the narrow gold tips with limited volume, thus, resulting in a highly enhanced electric field in the nano-cavity under illumination of the light wave. Reduction of the gap size between the two gold nano-tips, namely, the size of the nano-cavity, decreased the distance that the electric potential produced by the highly concentrated charges on the surface of each gold nano-tip had to jump across, therefore, causing a significantly enhanced field in the nano-cavity. Further, alignment of the linearly polarized electric field of the incident light wave with the symmetric axis of the PGNB efficiently enabled the free electrons in the PGNB to concentrate on the surface of the sharp gold tips with a high density, thus, strongly improving the field across the nano-cavity. The research provides a new insight for future design, nanofabrication, and characterization of PGNBs for applications in devices that relate to enhancing photons emission, improving efficiency for energy harvesting, and improving sensitivity for infrared detection.